Wave propagation in a one-dimensional diatomic periodic structure with high-static–low-dynamic stiffness and prestress effects - Vasconcellos, Diego Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
This work investigates wave propagation in a one-dimensional diatomic periodic structure with high static and low dynamic stiffness (HSLDS), subjected to different prestress conditions. Such structures exhibit bandgaps, frequency ranges in which wave propagation is suppressed, which are particularly relevant for vibration attenuation in lightweight systems like aerospace and automotive applications. The aim is to understand how geometric nonlinearity and prestress affect the formation and shifting of bandgaps, as well as low-frequency attenuation, with special emphasis on sensitivity to initial conditions analysed through basin of attraction studies. The methodology combines approaches such as mechanical impedance, dispersion relation, fourth-order Runge-Kutta integration, numerical continuation with MatCont, Poincaré sections, Lyapunov exponents, and basins of attraction. Linear results show that the mass ratio and number of unit cells strongly influence bandgaps, with good agreement between transmissibility and dispersion. In the nonlinear regime, prestress significantly alters the dynamics: under compression, quasi-periodic and chaotic responses prevail, while under tension, periodic responses dominate. The basins of attraction revealed multistability and coexistence of regimes, highlighting their importance in predicting dynamic behavior. It is concluded that prestress is an effective strategy for modifying bandgaps and attenuating low-frequency vibrations, representing a promising passive control technique. Moreover, the basin of attraction analysis stands out as a major contribution of this work, by demonstrating how sensitivity to initial conditions affects the predictability of nonlinear periodic structures.

Este trabalho investiga a propagação de ondas em uma estrutura periódica unidimensional diatômica com rigidez estática elevada e dinâmica reduzida (HSLDS), submetida a diferentes condições de pré-carga. Essas estruturas apresentam bandgaps, regiões de supressão de ondas relevantes para atenuação de vibrações em sistemas leves, com aplicações aeroespaciais e automotivas. O objetivo é compreender como a não linearidade geométrica e a pré-carga afetam a formação e o deslocamento dos bandgaps, bem como a atenuação em baixas frequências, com atenção especial à sensibilidade às condições iniciais analisada por meio das bacias de atração. A metodologia combina análises como: impedância mecânica, relação de dispersão, Runge-Kutta de quarta ordem, continuação no MatCont, seção de Poincaré, expoente de Lyapunov e bacias de atração. Os resultados lineares mostram que a razão de massa e o número de células unitárias influenciam os bandgaps, com boa concordância entre transmissibilidade e dispersão. No regime não linear, a pré-carga altera a dinâmica: sob compressão, predominam respostas quase-periódicas e caóticas, enquanto sob tração surgem respostas mais periódicas. As bacias de atração revelaram multistabilidade e coexistência de regimes, destacando sua importância para prever o comportamento dinâmico. Conclui-se que a pré-carga é uma estratégia eficaz para modificar bandgaps e atenuar vibrações em baixas frequências, podendo ser utilizada como uma técnica de controle passivo, e que a análise da bacia de atração constitui uma importante contribuição deste trabalho ao evidenciar a influência das condições iniciais na previsibilidade de estruturas periódicas não lineares.
Propagação de ondas em uma estrutura periódica diatômica unidimensional com rigidez estática alta e dinâmica baixa e efeitos de pré-carga
Keywords: Bandgap; Dispersion Relation; Geometric nonlinearity; Mass ratio; Periodic structure; Prestress; Wave propagation; Relação de dispersão; Não linearidade geométrica; Razão de massa; Estrutura periódica; Propagação de ondas